Nick Joaquin in Retrospect - Chua, Jonathan (Archīum Ateneo, 2017)
Excerpt: A man with two birthdays was Nick Joaquin. All sources agree that he was born Nicomedes Joaquin in 1917 in Paco, Manila, and one even gives the time of birth (“around 6:00 am”). But was it on May 4, as his passport indicates, or on September 15, the feast day of St. Nicomedes, that he “emerged from his mother’s womb . . . [and] made a big howling noise to announce his arrival”? Nick himself played coy, because “he hated having people come around to celebrate his birthday.”